S32 Hierarchical cluster analysis of subjects with severe asthma according to microbiological profile. (December 2018) - Diver, S; Richardson, M; Desai, D; Mistry, V; Haldar, K; Barer, M; Brightling, CE
Abstract : Background: Culture independent techniques demonstrate altered airway ecology in severe asthma at stable and exacerbation states. Biological cluster analysis across severe asthma and COPD has shown distinct cytokine and microbiological profiles, 1 suggesting that certain phenotypes may be more responsive to antimicrobial therapies. Previous work in COPD suggests that measuring the relative proportions of 2 dominant bacterial phyla, Gammaproteobacteria (G) and Firmicutes (F), or G:F ratio, may provide a useful biomarker to identify these groups. 2 Objective: To characterise subjects with stable severe asthma separated by cluster analysis according to airway microbiology. Methods: Patients with severe asthma were prospectively recruited to a single UK centre. Sputum samples were obtained from 63 clinically stable patients for microbiome analysis. Hierarchical cluster analysis according to phylum was performed and clinical characteristics compared between groups. Results: Three microbiological clusters were identified. Cluster 1 had a high G:F ratio and sputum microbial communities were dominated by the potentially pathogenic organisms Haemophilus and Moraxella (76% total pathogens). Clusters 2 and 3 had lower proportions of these organisms (23% and 7% respectively) with equivalent and low G:F ratios. Whilst no statistically significant difference in clinical characteristics was observed between groups, there was a trend towards increased bacterial load in cluster 1 (5.69 × 10 9 CFU/ml) compared to clusters 2 and 3 (1.41 and 2.84 × 10 9 CFU/ml, p=0.067). The high G:F group did not have a higher total neutrophil count or% neutrophil count as compared to other groups. There was no significant difference between clusters in exacerbations/year at baseline, as defined by either oral corticosteroid or antibiotic requirement. Conclusion: Microbiological clustering in severe asthma identifies three groups with significantly different G:F ratios. Further testing is required to ascertain whether this measure is a useful biomarker, for example, to identify those likely to respond to maintenance antibiotic therapy. References: Ghebre MA, Pang PH, Diver S, et al. Biological exacerbation clusters demonstrate asthma and chronic obstructive pulmonary disease overlap with distinct mediator and microbiome profiles. J Allergy Clin Immunol2018;141(6):2027–36 e12. Haldar K, Bafadhel M, Lau K, et al. Microbiome balance in sputum determined by PCR stratifies COPD exacerbations and shows potential for selective use of antibiotics. PLoS One2017;12(8):e0182833.